Late-presenting right congenital diaphragmatic hernia. A case report. - Zakaria Zoheir Addou (Batna Journal of Medical Sciences, 2023)
Congenital diaphragmatic hernia (CDH) is the absence of development of all or part of a diaphragmatic dome that allows the abdominal organs to move into the thorax. Right posterolateral hernia represents 15% of CDH cases and late forms 5 to 25% of cases. We report the case of an infant admitted to the emergency department for severe respiratory distress following a late-onset right congenital diaphragmatic hernia. The 05 months old infant presented to the emergency department with vomiting, severe respiratory distress with decreased right vesicular murmurs. Chest X-ray showed a white right lung field with aeration zones and chest CT showed a right diaphragmatic hernia. After stabilization of the patient's condition, surgery was performed which reveal strangulated digestive tracts through the right posterolateral diaphragmatic defect. The postoperative course was simple with a good outcome and no recurrence after 06 months of follow-up. Late-onset congenital HDC should be suspected by respiratory and digestive signs and confirmed by imaging. Surgery should be performed urgently and without delay.